INTEGRATING GREEN PRODUCT INNOVATION AND AI IN BUSINESS STRATEGIES FOR COMPETITIVE ADVANTAGE: A STUDY OF INDONESIAN'S FUTURE - Ardiansyah, Eka (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study delves into the synergy between green product innovation and artificial intelligence (AI) as a key to enhancing the competitive advantage of companies in Indonesia. A total of 15 manufacturing and retail companies were studied using a mixed methods approach, the results obtained showed that although awareness of the importance of both aspects is increasing, there are still a number of challenges in implementing an effective AI strategy. One of the main obstacles lies in the level of understanding of the workforce, where 75% of the data obtained indicated that AI users are not yet fully able to utilize the potential of this technology to increase sales. However, it is undeniable that the application of artificial intelligence can have a positive impact in terms of operational efficiency, resource management, and the development of more environmentally friendly products. Ultimately, this study is expected to provide valuable insights for companies in Indonesia that are ambitious to integrate green product innovation and artificial intelligence. The emphasis on the importance of intellectual capital is a crucial aspect to achieve this goal. These findings are expected to enrich the understanding of how companies in Indonesia can remain competitive in the global market while supporting sustainable practices, in order to achieve future success.